Unravelling the complexities of AI literacy : How do tertiary educational institutions equip their students with skills to embrace generative AI? - Kumar, Siddharth; Miklánek, Tomáš; Sáenz de Viteri Vázquez, Andrea; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Given the current rapid integration of generative AI technologies into a wide range of businesses, it is critical to evaluate students' readiness to navigate this technological environment as they enter the workforce. With the increasing prevalence and influence of generative AI, it is imperative that students acquire the requisite skills. Thus, the purpose of this research is to examine how tertiary education prepares students for the workforce by enabling them to adopt generative AI systems. By employing an in-depth literature review and structured interviews, nuanced insights about students’ viewpoints, experiences, and difficulties are presented. The findings furthermore indicate a discrepancy between the level of generative AI discourse in learning environments and the real transfer of critical competencies. Although some students have been introduced to generative AI, many do not have access to comprehensive training or real-world experience. This disparity implies that the studied institution may place more emphasis on cursory talks than in-depth instruction. Moreover, although students understand the value of ethical behaviour and critical thinking as crucial skills for generative AI, more organised instruction and practical experience are required to sufficiently prepare them for the labour market.
Vedoucí práce: Tomáš Miklánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses